First record of Synagelides Strand, 1906 (Araneae: Salticidae) from Sri Lanka: description of four endemic species from tropical wet forest of the island - Kanesharatnam, Nilani; Benjamin, Suresh P. (Zootaxa, 2020)
Synagelides Strand, 1906 is recorded for the first time in Sri Lanka. Four new species are described and illustrated: S. hortonensis sp. nov., S. lakmalii sp. nov., S. rosalindae sp. nov. and S. orlandoi sp. nov. A key to the four new species is given.